Clinical Evaluation of the Treatment Outcomes of Tue Tinh Gastric Capsules for Gastroduodenal Ulcers (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the efficacy of "Tue Tinh" stomach capsule in the supportive treatment of patients with peptic ulcer. Methods: A prospective, controlled clinical trial was conducted on 60 patients diagnosed with peptic ulcer (Qi stagnation and Fire stagnation pattern). Patients were divided into 2 groups: Study group (n=30) treated with "Tue Tinh" stomach capsules and Control group (n=30) treated with active control drugs for 28 days. Results: After 28 days, clinical symptoms in the study group improved significantly: epigastric pain reduced from 100% to 21.7%; belching, heartburn, and bloating reduced to below 10%; epigastric burning sensation decreased from 46.7% to 11.67%. Regarding overall efficacy, the Study group achieved 63.4% Good, 33.3% Fair, and only 3.3% Poor results. Compared to the Control group (53.4% Good; 16.6% Poor), the Study group showed higher efficacy with statistical significance (p < 0.05). Conclusion: "Tue Tinh" stomach capsule is effective in improving clinical symptoms and supporting the treatment of peptic ulcer, with a good safety profile.
Keywords: Gastroduodenal ulcers, Tue Tinh gastric capsules, Qi stagnation, fire stagnation.